Awareness of Language Norms as a Factor in the Maintenance of the Inge Ndai Language Within the Kinship Domain of the Lambitu Community - Rahmatia Ardila; Najamudin; M. Ade Wahyudin; M. Salahudin (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
The Lambitu community is a speech community that respects the norms and language rules practiced within society. This research aims to analyze Awareness of Language Norms as A Factor in the Maintenance of the Inge Ndai Language Within the Kinship Domain of the Lambitu Community. This research is qualitative. The data in this research consists of utterances that reflect the awareness of the norm. The data source consisted of the utterances of Inge Ndai speakers in the kinship domain. The data were collected using non-participant observation with recording and note-taking techniques. The data were analyzed using the identity method. The research findings indicate the awareness of norms factors as a form of Inge Ndai language maintenance in the kinship domain. Awareness of language norms is evident in the utterances spoken by close relatives: fathers, mothers, aunts, and sisters-in-law. Awareness of the language norm is also reflected in specific forms of Inge Ndai utterances, such as: (1) response particles (e.g., ’uu’ and ’ae’), (2) kinship terms of address (e.g., ’aa’, ’ama’, ’ipe’, ’ela’, ’dua’, and ’baba’), and (3) personal pronominal terms of address (e.g., ’rae’, ’eme’, and ’emera’). The benefits of this research: (1) to serve as a reference for future researchers in the field of sociolinguistics that investigates minority languages, (2) to enrich knowledge regarding regional language and the importance of maintenance, specifically the minority language with limited speakers.